1998
DOI: 10.1063/1.121456
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced nonlinear optical response of an endohedral metallofullerene through metal-to-cage charge transfer

Abstract: Copyright by the AIP Publishing. Heflin, JR; Marciu, D; Figura, C; et al., "Enhanced nonlinear optical response of an endohedral metallofullerene through metal-to-cage charge transfer," Appl. Phys. Lett. 72, 2788Lett. 72, (1998; http:// dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 24 publications
(22 reference statements)
2
28
0
Order By: Relevance
“…We have shown [45] that this overshooting effect is related with the donor ability of the substituent group. It has been observed that the overshooting monotonically increases with the donating ability of the donor as this is expressed by the Hammett parameter ı p [45]. The results of calculations for the static Į xx and ȕ xxx of molecules 1, 2 and 3 are presented in Table 2.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…We have shown [45] that this overshooting effect is related with the donor ability of the substituent group. It has been observed that the overshooting monotonically increases with the donating ability of the donor as this is expressed by the Hammett parameter ı p [45]. The results of calculations for the static Į xx and ȕ xxx of molecules 1, 2 and 3 are presented in Table 2.…”
Section: Resultsmentioning
confidence: 94%
“…In ref. 45 we have demonstrated that the usual functionals overestimate the first hyperpolarizability of 1. Some of these results are shown in Table1.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…EMFs hold great promise for applications in optoelectronic devices, since varying the encapsulated metal cluster can alter the optical and electronic properties without changing the structural features of the outer carbon shell. Enhancement of third-order nonlinear optical susceptibility observed in EMFs further establishes them as potential candidates for nonlinear optical devices (2,5). In early studies, La@C 60 was examined by Kroto et al, although it was never isolated in solid form (1,2).…”
Section: Introductionmentioning
confidence: 96%
“…Endohedral metallofullerenes (EMF) MC n (M = Sc, Y, and the majority of the lanthanides) are carbon clusters with metal atoms encapsulated inside the cage [34,35]. The unique structure, physical and chemical properties of EMFs are of great interest as new materials with unique magnetic, electrical and optical properties [36,37]. The production of EMFs is a real problem in studying the chemistry and physics of carbon clusters.…”
Section: Scientific Opportunitiesmentioning
confidence: 99%